2021
DOI: 10.5713/ajas.19.0874
|View full text |Cite
|
Sign up to set email alerts
|

Effect of JAK-STAT pathway in regulation of fatty liver hemorrhagic syndrome in chickens

Abstract: To explore the molecular mechanisms of fatty liver hemorrhagic syndrome (FLHS) in laying hens, an experiment was conducted to reveal the difference of histopathological observation and gene expression between FLHS group and normal group. Methods: We compared the histopathological difference using hematoxylin and eosin staining, and proceeded RNA sequencing of adipose tissue to search differentially expressed genes and enriched biological processes and pathways. Then we validated the mRNA expression levels by r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 36 publications
(49 reference statements)
3
10
0
1
Order By: Relevance
“…Fatty liver hemorrhagic syndrome-affected chickens had large, friable, and soft livers in contrast to healthy hens (Figure 1A), and the color varied from yellow to orange (Figure 1B), which is consistent with previous reports (Spurlock and Savage, 1993; Rozenboim et al, 2016;Zhu et al, 2020). Similar to the results we previously published (Zhu et al, 2020), there was no statistical difference in body weight between hens of the two groups, but the liver index of the FLHS group was significantly (P ≤ 0.01) higher than that of the healthy group (Table 1). Further, the concentrations of hepatic triglycerides (TG) and total cholesterol (TC) were much higher (P ≤ 0.01) than in healthy individuals (Table 1).…”
Section: Pathological and Histopathological Differences Between The Lsupporting
confidence: 91%
See 2 more Smart Citations
“…Fatty liver hemorrhagic syndrome-affected chickens had large, friable, and soft livers in contrast to healthy hens (Figure 1A), and the color varied from yellow to orange (Figure 1B), which is consistent with previous reports (Spurlock and Savage, 1993; Rozenboim et al, 2016;Zhu et al, 2020). Similar to the results we previously published (Zhu et al, 2020), there was no statistical difference in body weight between hens of the two groups, but the liver index of the FLHS group was significantly (P ≤ 0.01) higher than that of the healthy group (Table 1). Further, the concentrations of hepatic triglycerides (TG) and total cholesterol (TC) were much higher (P ≤ 0.01) than in healthy individuals (Table 1).…”
Section: Pathological and Histopathological Differences Between The Lsupporting
confidence: 91%
“…The featureCounts software (Liao et al, 2014) was used with "gene" as the feature and in strand-unaware mode. Lowly expressed genes (when the counts across 90% samples are lower than 2) were then removed, since those are usually more vulnerable to measurement errors as reported in our previous study (Zhu et al, 2020). The fragments per kilobase of transcript sequence per millions base pairs (FPKM) algorithm was used to normalize the expression of each gene.…”
Section: Rna Sequencing and Analysis Of Differential Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it was reported that Jak-STAT signaling pathway was downregulated in the blood sample of laying hens fed with a dried olive pomace, indicating that Jak-STAT signaling pathway is also correlated with amelioration of immune responses ( Iannaccone et al, 2019 ). This pathway was also highlighted in the adipose tissue of an experiment comparing with fatty liver hemorrhagic syndrome ( FLHS ) chickens and normal chickens ( Zhu et al, 2021 ). In the current study, similar upregulation of genes related to Jak-STAT signaling pathway in the liver were observed for WES group compared with SES group.…”
Section: Discussionmentioning
confidence: 94%
“…FLHS mostly occurs in caged layer hens during the peak period of egg production and in broiler breeders [ 1 , 2 ], which causes huge losses in the poultry industry. Many factors are considered to be possible causes of FLHS, but imbalanced nutrition is the major one [ 3 ], similar to nonalcoholic fatty liver disease (NAFLD) in humans [ 4 ]. NAFLD begins with insulin resistance, which is more common in birds than in mammals.…”
Section: Introductionmentioning
confidence: 99%